2013
DOI: 10.2174/1570159x11311040006
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo Biloba Extract in an Animal Model of Parkinson’s Disease: A Systematic Review

Abstract: Although the exact cause of neuronal loss in Parkinson’s disease is not known, evidence points to oxidative stress and the production of reactive oxygen species as the main events that occur in the substantia nigra pars compacta of the brain of parkinsonians. EGb761 is an extract of the leaves from the Ginkgo biloba tree that has been reported as an antioxidant and neuroprotective agent. The objective of this work was to perform a systematic review of the studies that analysed the effect of Ginkgo biloba extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 22 publications
0
15
0
1
Order By: Relevance
“…In addition to containing anti-inflammatory flavanoids and terpinoids, Ginko extract is thought to exhibit important effects on multiple neurotransmitter pathways including acting as an MAO-Inhibitor (MAOI), and inhibiting reuptake of serotonin, dopamine, and norepinephrine. While neuroprotective effects of these substances have been demonstrated in PD rat models, there are no randomized controlled clinical trials in humans using either ginko or ginseng in this population to guide recommendations[ 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to containing anti-inflammatory flavanoids and terpinoids, Ginko extract is thought to exhibit important effects on multiple neurotransmitter pathways including acting as an MAO-Inhibitor (MAOI), and inhibiting reuptake of serotonin, dopamine, and norepinephrine. While neuroprotective effects of these substances have been demonstrated in PD rat models, there are no randomized controlled clinical trials in humans using either ginko or ginseng in this population to guide recommendations[ 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…In another animal models of PD, which was induced by 1-methyl-4-phenylpyridinium, the authors found that EGb 761 could protect against neurotoxicity via preventing changes of copper content in the striatum, midbrain and hippocampus [ 97 ]. Tanaka systematically reviewed the effect of EGb in animal models of PD in 32 English language articles and found that most studies reported focused on EGb protection against neurotoxin, anti-oxidative stress, anti-apoptotic and reduced loss of the neurotransmitter, dopamine, in the striatum [ 98 ].…”
Section: The Effect Of Egb On Aging-related Diseasesmentioning
confidence: 99%
“…На модели БП была показана эффективность EGb761 как нейропротектора с восстанавливающими свойствами, эффективно предотвращающего гибель дофаминергических нейронов среднего мозга. EGb761 показал способность уменьшать степень двигательных расстройств у экспериментальных животных, что позволяет рекомендовать его в качестве адъювантного препарата для лечения БП [46].…”
Section: болезнь паркинсонаunclassified